2013
DOI: 10.1007/s10653-013-9570-7
|View full text |Cite
|
Sign up to set email alerts
|

Haematological changes in fluorotic adults and children in fluoride endemic regions of Gaya district, Bihar, India

Abstract: Groundwater used for drinking and cooking was analysed for fluoride (F), and health surveys were conducted in Bodh Gaya, Amas and Bankebazaar blocks of the Gaya district, Bihar, India. Amas and Bankebazaar blocks were F endemic areas with mean F = 2.36 ± 0.23 mg/L (N = 27). Bodh Gaya was considered as control area with mean F = 0.59 ± 0.03 mg/L (N = 11). Health survey showed that more than 50 % of adults and more than 55 % of children had complaints of gastro-intestinal (GI) disturbances in the F endemic areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In our present study, the serum F content was markedly higher in the three high F groups than that in the control group at 42 days of age (p < 0.01). The increased content of serum F was reported by many anthors [17]- [19]. Likewise, the content of urine F significantly increases in rat [20], rabbit [18] and fluorotic human [19] has been reported.…”
Section: Effects Of High Dietary F On the Content Of Serum F In Broilmentioning
confidence: 79%
See 1 more Smart Citation
“…In our present study, the serum F content was markedly higher in the three high F groups than that in the control group at 42 days of age (p < 0.01). The increased content of serum F was reported by many anthors [17]- [19]. Likewise, the content of urine F significantly increases in rat [20], rabbit [18] and fluorotic human [19] has been reported.…”
Section: Effects Of High Dietary F On the Content Of Serum F In Broilmentioning
confidence: 79%
“…The increased content of serum F was reported by many anthors [17]- [19]. Likewise, the content of urine F significantly increases in rat [20], rabbit [18] and fluorotic human [19] has been reported. Kono et al [21] reported that serum F concentrations in F-exposed workers with impaired renal function were strikingly higher than in other patients with chronic renal failure (CRF) and F-exposed workers.…”
Section: Effects Of High Dietary F On the Content Of Serum F In Broilmentioning
confidence: 79%
“…It is well established that fluoride damages not only hard tissues (teeth and bones) but also various soft tissues including blood cells. In recent studies, it has been concluded that excess fluoride exposure accelerates various hematological degenerations leading to erythrocyte death and anaemia [85][86][87]. In tribals, sickle cell disease and β-thalassaemia major are also fatal and cause varying degrees of anemia in tribal adults and children, respectively [25].…”
Section: Sickle Cell Anaemia (Hb-ss) and Fluoride Poisoning In Tribalsmentioning
confidence: 99%
“…Chronic F exposure for prolonged period destructs both hard (teeth and bones) and soft tissues including blood cells. Recently, in the study it has been claimed that excess ingestion of F for long-time or chronic F exposure from industrial F pollution causes various haematological degenerative changes leading to death of erythrocytes and causing mild to severe anaemia [104][105][106]. In the present tribal scheduled area, certain lethal erythrocyte genetic disorders such as sicklecell anaemia and β-thalassaemia major are also prevalent and causing mild to severe anaemia in adults and children, respectively [11].…”
Section: Impact Of Excess F Ingestionmentioning
confidence: 99%